1995
DOI: 10.1038/bjc.1995.360
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in incidence of and mortality from breast, ovarian and endometrial cancers in England and Wales and their relation to changing fertility and oral contraceptive use

Abstract: Summary Reproductive-related factors play a major role in the aetiology of cancers of the breast, ovary and endometrium. Pregnancy history influences the risk of each of these cancers, and oral contraceptive use modifies the risks of ovarian and endometrial cancers, although its effect on breast cancer risk is less certain. We analysed recent time trends in the incidence and mortality of these cancers in England and Wales and assessed whether they can be explained by changes in fertility and oral contraceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
7

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
3
28
0
7
Order By: Relevance
“…Incidence has been reported to have increased for several decades up to the early 1980s, [12][13][14] while subsequently some declines have been reported in East Germany, 17 Sweden, 15 Switzerland 18 and England and Wales. 16,19 The results presented here are in accordance with these previous reports and update and expand the analysis to countries where trends have not been reported. Further, the systematic approach utilised in this study, allowing a Europe-wide description of the contrasting variations in secular incidence and mortality trends, is a useful tool to better understand the causes of corpus uteri cancer and how best to develop effective population-specific prevention strategies.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Incidence has been reported to have increased for several decades up to the early 1980s, [12][13][14] while subsequently some declines have been reported in East Germany, 17 Sweden, 15 Switzerland 18 and England and Wales. 16,19 The results presented here are in accordance with these previous reports and update and expand the analysis to countries where trends have not been reported. Further, the systematic approach utilised in this study, allowing a Europe-wide description of the contrasting variations in secular incidence and mortality trends, is a useful tool to better understand the causes of corpus uteri cancer and how best to develop effective population-specific prevention strategies.…”
Section: Discussionsupporting
confidence: 81%
“…37 Combined oral contraceptives became increasingly available after their introduction in the 1960s, and their use has become widespread among women of reproductive age, particularly in higher-resource countries, where long-term use is common. 38 Previous studies examining incidence trends in Europe have noted a decline in young women, [15][16][17][18][19] several attributing the observations to oral contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nulliparity decreased in most European countries for cohorts born from 1930 to 1945 (32). In England and Wales, where data are available for a longer period, the decline in nulliparity began for cohorts born since 1910 (15). A recent study indicated that reproductive patterns may account for about half of the cases of endometrial cancer in Sweden in women diagnosed from 1961 to 2002 (33), although the importance of reproductive behavior on risk has been shown to decrease at older ages (34).…”
Section: Endometrial Cancer Incidence Trends In Europementioning
confidence: 99%
“…More recent studies in Sweden (11), East Germany (12), Switzerland (13), and the United Kingdom (14-16) have indicated steady declines in endometrial cancer incidence rates among younger women and in more recent birth cohorts. Most have attributed this phenomenon to the increasing prevalence of COC use (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%